HEALTH RISK ASSESSMENT OF PESTICIDE EXPOSURE AMONG LOCAL VEGETABLE FARMERS IN BUNGWAI SUBDISTRICT, WARIN CHAMRAP DISTRICT, UBON RATCHATHANI PROVINCE - Boonkhao, Laksanee; Malasee, Jittisak; Toson, Rujira; Lamee , Sirapa (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This cross-sectional study aimed to assess health risks of exposure to organophosphate and carbamate pesticides among 95 local vegetable farmers who grew Limnophila aromatic and Centella asiatica at Bungwai Subdistrict, Warin Chamrap District, Ubon Ratchathani Province. Data were collected using questionnaires and the health risk assessment form by the Department of Disease Control. Risk levels were assessed using a 5-point scale: very high, high, relatively high, medium, and low. Data were analyzed using frequency counts and percentages. The results showed that 72.53% of the farmers were at the low risk for pesticide exposure, 24.17% of them were at the medium risk, and 3.30%of them had the relatively high risk of being exposed to pesticides. However, there were pesticide risk behaviors among the farmers. The research found that 35.16% of them always used pesticides in their farming operations and 29.67% of them did not change their pesticide-contaminated clothes immediately after spraying the pesticides. It also found that 28.57% and 25.27% of the farmers did not immediately wash their bodies when their clothes were soaked with chemicals and did not wear boots or shoes to protect themselves from pesticides, respectively. In addition, 15.38% of them experienced symptoms of fatigue, headache, and itchy skin after being exposed to pesticides. Therefore, the concerned authorities should encourage safe pesticide practices among the farmers and promote organic farming to reduce the risks of pesticide exposure among the farmers.